Acupuncture and electro‐acupuncture for people diagnosed with subacromial pain syndrome: A multicentre randomized trial. (20th January 2017) - Lewis, J.; Sim, J.; Barlas, P.
Abstract: Background: Musculoskeletal disorders have been identified globally as the second most common healthcare problem for 'years lived with disability', and of these shoulder conditions are amongst the most common, frequently associated with substantial pain and morbidity. Exercise and acupuncture are often provided as initial treatments for musculoskeletal shoulder conditions but their clinical effectiveness is uncertain. This study compared group exercise with group exercise plus either acupuncture or electro‐acupuncture in patients with subacromial pain syndrome. Methods: Two hundred and twenty‐seven participants were recruited to a three‐arm parallel‐group randomized clinical trial. The primary outcome measure was the Oxford Shoulder Score. Follow‐up was post treatment, and at 6 and 12 months. Between‐group differences (two comparisons: the exercise group versus each of the acupuncture groups) were analysed at 6 months. A similar comparison across all follow‐up time points was also conducted. Data were analysed on intention‐to‐treat principles with imputation of missing values. Results: Treatment groups were similar at baseline, and all treatment groups demonstrated an improvement over time. Between‐group estimates at 6 months were, however, small and non‐significant, for both of the comparisons. The analyses across all follow‐up time points yielded similar conclusions. There was a high rate of missing values (22% for the Oxford Shoulder Score). A sensitivity analysis using complete data gave similar conclusions to the analysis with missing values imputed. Conclusions: In the current investigation, neither acupuncture nor electro‐acupuncture were found to be more beneficial than exercise alone in the treatment of subacromial pain syndrome. These findings may support clinicians with treatment planning. Significance: Shoulder pain is common and associated with substantial morbidity. Acupuncture is a popular treatment for shoulder pain. The findings suggest that acupuncture and electro‐acupuncture offer no additional benefit over exercise in the treatment of shoulder pain of musculoskeletal origin.